Ki-67 staining in histological subtypes of breast carcinoma and fine needle aspiration smears. - Kuenen-Boumeester, V (1991)
Thirty four cases of invasive breast carcinoma were analysed for heterogeneity of Ki-67 reactivity in a tumour, and proliferative activity in various histological subtypes was compared. The growth factions determined in areas of central and peripheral tumour were the same. Mucinous and lobular carcinoma showed lower Ki-67 activity than ductal carcinomas. When ductal carcinomas were subdivided according to their dominant growth pattern, the carcinomas with a solid or comedo growth pattern showed the highest proliferative activity. These results largely confirm data from previous cell kinetic studies on the incorporation of radioactively labelled thymidine. A correlation between the growth fraction determined by Ki-67 in fine needle aspiration smears and cryostat sections of corresponding tumours was shown, implying that the immunostaining of cytological smears gives a reliable impression of the growth fraction of a tumour and may therefore be used in prospective studies.